2012
DOI: 10.5005/jp-journals-10006-1184
|View full text |Cite
|
Sign up to set email alerts
|

GNK-PIMS Score: A Predictive Model for Success of External Cephalic Version

Abstract: Objective: To determine association of GNK-PIMS score vs Newmann Peacock score with success of external cephalic version (ECV). Materials and methods:This comparative cross-sectional analysis was carried out at MCH center Unit I, PIMS, Islamabad, from 1st January 2006 to 31st December 2009. Characteristics of 166 breech versions performed during study period were integrated into both Newmann Peacock score and GNK-PIMS score. Association of the two scoring systems with success of ECV was determined using Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 11 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…In our study, the type of breech also showed significant association with successful ECV similar to results of Tasnim et al & Burgos et al 25,26 but contrary to the Newman predictive scoring which suggested an insignificant association of type of breech with ECV success. In our sample, we had 24 extended breech, out of which 19 remained breech & only 5 converted to cephalic on ECV.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the type of breech also showed significant association with successful ECV similar to results of Tasnim et al & Burgos et al 25,26 but contrary to the Newman predictive scoring which suggested an insignificant association of type of breech with ECV success. In our sample, we had 24 extended breech, out of which 19 remained breech & only 5 converted to cephalic on ECV.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, there is only one published study about the performance of this prognostic system in a Pakistani obstetrical setting of 116 women, showing high failure rates regarding scores 3 (93.8%), and a similar failure rate regarding higher scores (40-46%). 9 Considering the potential benefit Conclusions The Newman-Peacock score had a poorer performance among our population compared to its performance in the original study, but the results suggest that this score is still a useful tool to guide our clinical practice and counsel the candidate regarding ECV.…”
Section: Introductionmentioning
confidence: 79%
“…Burgos et al 17 published a larger 2-phase study in 2011 with 500 and then another 500 women, and suggested another index that only included parity, placental location, type of breech and amount of amniotic fluid, with a predictability of 73.8%. Tasnim et al 9 proposed a score that included BMI, parity, gestational age, type of breech and AFI as predictors, which were chosen after an observational phase study with 267 women, with a better prediction performance than the Newman-Peacock score, but without a prospective validation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study quality assessment based on the signaling questions are shown in Table 4. Out of 17 new articles, 10 studies were identi ed as having low overall risk of bias and high study quality 22,[33][34][35][36]39,41,[44][45][46] , 6 studies were identi ed as having moderate bias and moderate study quality 29,37,38,42,43,47 , and 1 was considered to have high bias and low quality 30 . This is in addition to Velzel et al's assessment of the 8 prior articles of which 4 were low risk of bias and high study quality and 4 were moderate risk of bias and study quality 10 .…”
Section: Quality and Biasmentioning
confidence: 99%
“…While the large majority of articles studied maternal weight or BMI, only a few indicated whether this was collected or intended to be a pregravid, peri-ECV, or peripartum BMI. Of the 8 models using some form of maternal weight or BMI, one model used BMI at ECV 46 , one model used the BMI increase from prepregnancy to ECV 39 , two models from the same article used pre-pregnancy BMI 36 , and 4 models were not clear on when BMI was evaluated 30,31,41,44 .…”
Section: Predictor Variablesmentioning
confidence: 99%